CDS Auctions - Chernov, Mikhail; Gorbenko, Alexander S.; Makarov, Igor (Review of Financial Studies, 2013)
We analyze auctions for the settlement of credit default swaps (CDS) theoretically and evaluate them empirically. The requirement to settle in cash with an option to settle physically leads to an unusual two-stage process. In the first stage, participants affect the amount of the bonds to be auctioned off in the second stage. Participants in the second stage may hold positions in derivatives on the assets being auctioned. We show that the final auction price might be either above or below the fair bond price because of strategic bidding on the part of participants holding CDS. Empirically, we observe both types of outcomes, with undervaluation occurring in most cases. We find that auctions undervalue bonds by an average of 6% on the auction day. Undervaluation is related positively to the amount of bonds exchanged in the second stage of the auction, as predicted by the theory. We suggest modifications of the settlement procedure to minimize the underpricing.